2011
DOI: 10.1242/dev.068866
|View full text |Cite
|
Sign up to set email alerts
|

The roles of maternal Vangl2 and aPKC inXenopusoocyte and embryo patterning

Abstract: SUMMARYThe Xenopus oocyte contains components of both the planar cell polarity and apical-basal polarity pathways, but their roles are not known. Here, we examine the distribution, interactions and functions of the maternal planar cell polarity core protein Vangl2 and the apical-basal complex component aPKC. We show that Vangl2 is distributed in animally enriched islands in the subcortical cytoplasm in full-grown oocytes, where it interacts with a post-Golgi v-SNARE protein, VAMP1, and acetylated microtubules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 52 publications
(59 reference statements)
4
37
0
Order By: Relevance
“…Indeed, both cortical and nuclear enrichment of β-catenin is known to take place in worm embryonic cells in response to different Wnt signaling branches (Sawa, 2012; Schneider and Bowerman, 2007; Sugioka et al, 2011). Consistent with the above hypothesis, Vangl2 has been proposed to play a role in Xenopus oocyte polarity (Cha et al, 2011). Additional experiments are warranted to investigate these new functions of PCP proteins in animal-vegetal and dorsal-ventral axis specification.…”
Section: Role Of Wnt Signaling In Embryonic Axis Specificationsupporting
confidence: 52%
“…Indeed, both cortical and nuclear enrichment of β-catenin is known to take place in worm embryonic cells in response to different Wnt signaling branches (Sawa, 2012; Schneider and Bowerman, 2007; Sugioka et al, 2011). Consistent with the above hypothesis, Vangl2 has been proposed to play a role in Xenopus oocyte polarity (Cha et al, 2011). Additional experiments are warranted to investigate these new functions of PCP proteins in animal-vegetal and dorsal-ventral axis specification.…”
Section: Role Of Wnt Signaling In Embryonic Axis Specificationsupporting
confidence: 52%
“…Recruitment of fly Van Gogh to the plasma membrane is thought to be a crucial event for PCP signaling in epithelial cells (Strutt and Strutt, 2009). However, recent in vitro and in vivo studies have identified VANGL2 expression within vesicular compartments (Merte et al, 2010;Cha et al, 2011). VANGL2 and MMP14 colocalization in HT-1080 cells was detected at the plasma membrane ( Fig.…”
Section: Vangl2 Regulates Mmp14 Endocytosismentioning
confidence: 87%
“…These observations further expand the spectrum of PCP-associated morphogenetic processes. Besides planar epithelial polarity, PCP proteins were reported to affect mitotic spindle orientation and cell differentiation (Bellaiche et al, 2004;Cortijo et al, 2012;Lake and Sokol, 2009), cilia positioning (Hashimoto et al, 2010;Song et al, 2010), axon guidance (Lyuksyutova et al, 2003;Tissir and Goffinet, 2013), apical-basal polarity , oocyte development (Cha et al, 2011) and migration of endodermal (Trichas et al, 2012), germ cell (Laird et al, 2011) and neuronal progenitors (Carreira-Barbosa et al, 2003;Glasco et al, 2012;Jessen et al, 2002). Additionally, Vangl2 and Rock are involved in lung branching morphogenesis (Yates et al, 2010b), and both Vangl2 and Daam1 were reported to function in kidney tubulogenesis (Miller et al, 2011;Yates et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%